Feasibility, Acceptability, and Programme Effectiveness of Misoprostol for Prevention of Postpartum Haemorrhage in Rural Bangladesh: A Quasiexperimental Study - Abdul Quaiyum; Rukhsana Gazi; Shahed Hossain; Andrea Wirtz; Nirod Chandra Saha (Hindawi Limited, 2014)
We explored the feasibility of distributing misoprostol tablets using two strategies in prevention of postpartum haemorrhage (PPH) among women residing in the Abhoynagar subdistrict of Bangladesh. We conducted a quasiexperimental study with a posttest design and nonequivalent comparison and intervention groups. Paramedics distributed three misoprostol tablets, one delivery mat (Quaiyum's delivery mat), a packet of five standardized sanitary pads, and one lidded plastic container with detailed counseling on their use. All materials except misoprostol were also provided with counseling sessions to the control group participants. Postpartum blood loss was measured by paramedics using standardized method. This study has demonstrated community acceptability to misoprostol tablets for the prevention of PPH that reduced overall volume of blood loss after childbirth. Likewise, the delivery mat and pad were found to be useful to mothers as tools for assessing the amount of blood loss after delivery and informing care-seeking decisions. Further studies should be undertaken to explore whether government outreach health workers can be trained to effectively distribute misoprostol tablets among rural women of Bangladesh. Such a study should explore and identify the programmatic requirements to integrate this within the existing reproductive health program of the Government of Bangladesh.